2013
DOI: 10.1002/mrd.22185
|View full text |Cite
|
Sign up to set email alerts
|

Bora regulates meiotic spindle assembly and cell cycle during mouse oocyte meiosis

Abstract: Bora is the binding partner of Aurora A, which is required for its activation and phosphorylation of Polo like kinase 1 (Plk1), and is involved in the spindle assembly and progress of the cell cycle during mitosis. In this study, we examined the expression, localization, and function of Bora during mouse oocyte meiosis. The expression level of Bora was increased during oocyte meiotic maturation, with an elevated level at metaphase. Immunofluorescence analysis showed that Bora was concentrated as a dot shortly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…We thus conclude that, similar to what happens in somatic cells and mouse oocytes, 26 Bora is present in CSF extract, and its degradation is mediated by Cdk1, Plx1, and the SCF β-TrCP . However, in contrast to somatic cells, degradation of Bora in CSF extracts apparently requires an additional step triggered by calcium.…”
Section: Bora Degradation By Scfsupporting
confidence: 66%
See 1 more Smart Citation
“…We thus conclude that, similar to what happens in somatic cells and mouse oocytes, 26 Bora is present in CSF extract, and its degradation is mediated by Cdk1, Plx1, and the SCF β-TrCP . However, in contrast to somatic cells, degradation of Bora in CSF extracts apparently requires an additional step triggered by calcium.…”
Section: Bora Degradation By Scfsupporting
confidence: 66%
“…Bora has recently been identified in mouse oocytes; 26 however, we wondered whether Xenopus oocytes also express endogenous Bora. According to unigene transcript data (http://www.ncbi.…”
Section: Bora Degradation By Scfmentioning
confidence: 99%
“…28 In addition, Bora, known as a binding partner of Aurka, regulates the precise localization of Aurka and Plk1. 29 The protein expression of Bora was significantly reduced, and the levels of Plk1, phosphorylated Tpx2 also showed a decreasing tendency following Bcl2l10 RNAi (Fig. 6A and B).…”
Section: Bcl2l10 Rnai Reduces Mtoc-associated Protein Expressionmentioning
confidence: 91%
“…We expected to identify a new protein that phosphorylates Plk1 and maintains Plk1 phosphorylation in Bcl2l10 RNAi-treated oocytes. Although the expression patterns and functions of these genes in oocyte meiosis were in many ways unlike those in mitosis, 15,29,39,44 it could be concluded that Bcl2l10 is strongly engaged as a part of the cascade of the BoraPlk1-Tpx2-Aurka pathway for regulating meiosis.…”
Section: Bcl2l10 Controls Meiotic Spindle Assembly By Regulating Mtocmentioning
confidence: 99%
“…Inspection of these arrested embryos revealed loss of AURKA at spindles and defective microtubule nucleation. In addition to TPX2, Bora , another AURKA binding partner, is critical for the localization and activation of AURKA at spindle poles in mouse oocytes [35]. In wild-type oocytes Bora co-localizes with AURKA at spindle poles and depletion of Bora using siRNA disrupts AURKA localization and results in abnormal spindle morphologies and misaligned chromosomes at Met I.…”
Section: Aurora Kinasesmentioning
confidence: 99%